Course of dentistry - Burega, Yu. O.; Maslova, I. M.; Бурега, Юрій Олексійович; Маслова, Ірина Миколаївна (Zaporizhzhia state medical university, 2016)
Dentistry is an espessialy and separate branch of medicine that is involved in the study, diagnosis, prevention, and treatment of diseases, disorders and conditions of the oral cavity, commonly in the dentition but also the oral mucosa, and of adjacent and related structures and tissues, particularly in the maxillofacial (jaw and facial) area. Its includes Oral and Maxillofacial surgery specializes in treating many diseases, injuries and defects in the head, neck, face, jaws and the hard and soft tissues of the Oral (mouth) and Maxillofacial (jaws and face) region. It is an internationally recognized surgical specialty. Prepare a general medical profile is impossible without mastering the basics of dentistry of dental care. To achieve this, students need to pay great attention to the etiology and prevention of dental diseases, the importance of environmental factors, occupational hazards, exposure dental status on the course of systemic diseases, be familiar with congenital and acquired defects of maxillofacial area, course and treatment of dental diseases.